RANCANG BANGUN SISTEM INFORMASI GEOGRAFIS PEMETAAN LOKASI PERUSAHAAN REKAN LEMBAGA KARIR KAMPUS - Riski Annisa (STMIK KAPUTAMA, 2020)
The internet is a technology that is growing rapidly. The internet creates a new world without limits. This affects humans in searching for information. One of the information needed by the community at this time is the need for geographical information. Geographic Information System is a geographic technology that has the ability to visualize spatial data and its attributes. Campus career institute is a field that moves to facilitate alumni or students who want to find work. In this collaboration there are several obstacles according to the author in collecting information about the company. At present the information is only in the form of non-spatial data. Then we need a geographic information system (GIS) to facilitate the mapping of company locations.